Affecting factors of consumer attitudes to using e-payment: Context of Saudi market - Helmi, Majed A. (Edelweiss Applied Science and Technology, 2025)
The demand for electronic payment (e-payment) systems in recent years has grown steadily, with a notable acceleration during the COVID-19 pandemic. Numerous studies have investigated user intentions and perceptions regarding the adoption of e-payment technologies. Building on this body of research, the present study proposes a conceptual model that integrates behavioral factors with the Technology Acceptance Model (TAM) to gain deeper insights into consumers’ use of e-payment systems. This study aims to identify key factors that influence users’ intention to use e-payment. The researcher designed the study to examine factors that influence consumers’ attitudes toward using e-payment, including security, trust, ease of use, perceived usefulness, and e-payment rewards. A quantitative research approach was employed, utilizing an online survey completed by 215 Saudi citizens. The findings reveal that all the identified factors positively influence user attitudes and intentions toward e-payment usage. Notably, perceived usefulness and ease of use emerged as direct predictors of user behavior. Future research should broaden the range of influencing factors considered in assessing consumer attitudes, such as social influence, and should include control groups based on gender to explore potential demographic differences.